2016
DOI: 10.1128/jcm.00960-16
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Antifungal Susceptibility of Penicillium-Like Fungi from Clinical Samples in the United States

Abstract: bPenicillium species are some of the most common fungi observed worldwide and have an important economic impact as well as being occasional agents of human and animal mycoses. A total of 118 isolates thought to belong to the genus Penicillium based on morphological features were obtained from the Fungus Testing Laboratory at the University of Texas Health Science Center in San Antonio (United States). The isolates were studied phenotypically using standard growth conditions. Molecular identification was made u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 40 publications
4
40
0
7
Order By: Relevance
“…Sequence of isolate LSP6 (ntseq 2) was identical to P. glabrum sequences GQ367506 (Barreto, Houbraken, Samson, Frisvad, & San-Romao, 2011) and KM088722 . Sequences of isolates LSP10 and LC3 (ntseq 3) were identical with P. glabrum sequences LT559031, | 665 DUDUK et al -Suarez et al, 2016) and KF225079 (Lecellier et al, 2014). Ntseq 2 and 3 shared 98% similarity with ntseq 1 and differed from it in eight and seven nucleotides, respectively.…”
Section: Molecular Identificationmentioning
confidence: 80%
See 1 more Smart Citation
“…Sequence of isolate LSP6 (ntseq 2) was identical to P. glabrum sequences GQ367506 (Barreto, Houbraken, Samson, Frisvad, & San-Romao, 2011) and KM088722 . Sequences of isolates LSP10 and LC3 (ntseq 3) were identical with P. glabrum sequences LT559031, | 665 DUDUK et al -Suarez et al, 2016) and KF225079 (Lecellier et al, 2014). Ntseq 2 and 3 shared 98% similarity with ntseq 1 and differed from it in eight and seven nucleotides, respectively.…”
Section: Molecular Identificationmentioning
confidence: 80%
“…Based on partial β-tubulin gene sequences two isolates (LC2 and LSP12) were identified as P. polonicum, four isolates (LSP3, LSP6, LSP10 and LC3) as P. glabrum and one isolate (LUB) as P. expansum (Table 1). Both sequences of P. polonicum isolates were identical and showed 99% similarity (one nucleotide difference) with the sequence AY674307 of P. polonicum CBS 69077 (Samson, Seifert, Kuijpers, Houbraken, & Frisvad, 2004) and were identical with P. polonicum sequences KJ545631 (Dugan et al, 2014), LT559042 and LT559042 (Guevara-Suarez et al, 2016). The sequence of isolate LUB differed in one nucleotide and was 99% similar to the P. expansum sequence CBS 32548 (AY674400) .…”
Section: Molecular Identificationmentioning
confidence: 88%
“…28 Indeed, it has been reported that a 57-year-old woman suffered from necrotizing pneumonia caused by P. chrysogenum. chrysogenum is known to be able to act as a pathogen and/or an allergen, inducing serious intoxication and damage to humans.…”
Section: Bioburden Testingmentioning
confidence: 99%
“…28 Indeed, it has been reported that a 57-year-old woman suffered from necrotizing pneumonia caused by P. chrysogenum. 28 Interestingly, a recent study demonstrated that P. rubens could produce a mycotoxin, ochratoxin A, which can cause intoxication of the kidneys and the liver. 30 Even a patient without immunological deficiencies was not exempted from central nervous system infection due to this mold.…”
Section: Bioburden Testingmentioning
confidence: 99%
See 1 more Smart Citation